Plasma volume variation across the menstrual cycle among healthy women of reproductive age: A prospective cohort study. Issue 8 (23rd April 2020) - Aguree, Sixtus; Bethancourt, Hilary J.; Taylor, Leigh A.; Rosinger, Asher Y.; Gernand, Alison D.
Abstract: Increases in reproductive hormones like estrogen, play an important role in the remarkable increases in plasma volume observed in pregnancy. Accurate estimates of plasma volume expansion during pregnancy depend on correctly timing and measuring plasma volume in nonpregnant women. However, to date, there is no consensus on the pattern of plasma volume across the menstrual cycle. We prospectively measured plasma volume in 45 women across a single menstrual cycle. A urine‐based fertility monitor was used to time three clinic visits to distinct points in the menstrual cycle: the early follicular phase (~day 2), periovulation (~day 12), and the mid‐point of the luteal phase (~day 21)—based on a 28‐day cycle length. Healthy women aged 18–41 years with regular menstrual cycles and a healthy body weight were enrolled in the study. At each visit, blood samples were collected before and after injection of 0.25 mg/kg body weight of indocyanine green dye (ICG). Pre‐ and post‐ICG injection plasma samples were used to measure plasma volume. Preinjection samples were used to measure ovarian hormones and plasma osmolality. Mean plasma volume was highest during the early follicular phase (2, 276 ± 478 ml); it declined to 2, 232 ± 509 ml by the late follicular phase and to 2, 228 ± 502 ml by the midluteal phase. This study found that overall variations in plasma volume are small across the menstrual cycle. Therefore, in clinical practice and research, the menstrual cycle phase may not be an important consideration when evaluating plasma volume among women of reproductive age. Abstract : In this study, we timed plasma volume measurements based on the pattern of change in estrogen and progesterone concentrations, across the menstrual cycle. We showed that plasma volume remained stable across the menstrual cycle irrespective of the concentration of estrogen and progesterone. Our data established that plasma volume measurements can occur at any timepoint across the menstrual cycle, and that estimates are not impacted by physiological fluctuations observed in estrogen and progesterone concentrations in women of reproductive age.